KONSEP SISI BASYARIYAH NABI MUHAMMAD SAW DAN PENGARUHNYA TERHADAP SUNNAH - Muhammad Sobirin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
This paper explores the basyariyah (human) dimension of the Prophet Muhammad SAW and its influence on the understanding of the Sunnah in Islam. The main focus of the study is to distinguish between tasyri’iyah Sunnah (normative/legal aspects) and non-tasyri’iyah Sunnah (human or cultural aspects), while highlighting the urgency of contextual interpretation of Sunnah in contemporary times. Employing a qualitative approach through literature review of both primary sources (the Qur’an and Hadith) and secondary sources, the study reveals that the Prophet’s human dimension encompasses aspects of character, actions, physical traits, and emotional responses, many of which are not directly tied to legal rulings. A proportional understanding of these two forms of Sunnah is essential to avoid homogenizing all of the Prophet’s actions, especially in light of evolving socio-cultural realities. The study emphasizes the need to distinguish between normative and human-contextual Sunnah as a foundation for relevant and wise religious practice.